General regularities of the microstructure formation during friction stir welding and sliding friction; Journal of Friction and Wear; Vol. 36, iss. 2 - Kolubaev A. V. Aleksander Viktorovich; Kolubaev Е. А. Evgeny Aleksandrovich; Sizova O. V. Olga Vladimirovna; Zaikina A. A. Anastasiya Andreevna; Rubtsov V. E. Valery Evgenjevich; Tarasov S. Yu. Sergei Yulievich; Vasiljev P. A. Petr Anatoljevich (2015, 2015)
Title screen